2017
DOI: 10.1039/c6ra27286j
|View full text |Cite
|
Sign up to set email alerts
|

Development of a harvesting technique for large-scale microalgal harvesting for biodiesel production

Abstract: Harvesting methods executed in lab and large-scale for efficient and sustainable harvesting of microalgae and supernatant reuse for recultivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Mixing using a paddle-wheel system may provide a better flocculation performance as the mechanism less disruptive to the large flocs as they pass through. Koley et al (2017) have demonstrated the effectivity of chitosan with flocculation efficiencies of ∼90% to flocculate Scenedesmus obliquus and Chlorella vulgaris cultured in raceway ponds. However, the cultures had to be pumped into 1000-L tanks, which was easier to mix with a large motor-driven stirrer.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing using a paddle-wheel system may provide a better flocculation performance as the mechanism less disruptive to the large flocs as they pass through. Koley et al (2017) have demonstrated the effectivity of chitosan with flocculation efficiencies of ∼90% to flocculate Scenedesmus obliquus and Chlorella vulgaris cultured in raceway ponds. However, the cultures had to be pumped into 1000-L tanks, which was easier to mix with a large motor-driven stirrer.…”
Section: Discussionmentioning
confidence: 99%
“…The high efficiency can be explained as chitosan has dual characteristics of charge neutralization and bridging, where protonated amine and hydroxyl groups mark chitosan as a good adsorbent. These active sites increase the surface interaction of chitosan with microalgal cells and assist in bridging and sedimentation of the cells [37].…”
Section: Organic Flocculantsmentioning
confidence: 99%
“…The mechanism behind is, wWhen the alum is added to the aqueous medium, aluminum hydroxide is formed, which is cationic in nature. The formation of superficial cationic charge interacts with negatively charged microalgal cells and hence neutralization of charge occurs as a result, cells forms flocs and settle [37]. FeCl3 is trivalent cation, which has been reported with 100 times higher flocculation efficiency than monovalent cations [56].…”
Section: Tablementioning
confidence: 99%
“…Before cultivation in raceway ponds, the selected microalga was scaled-up in the UZn medium (Koley, Mathimani, Bagchi, Sonkar, & Mallick, 2019), and was acclimatized to the outdoor condition as detailed in Sonkar, Deb, & Mallick (2020). The raceway ponds were operated at 30 cm of culture depth with a corresponding culture volume of 16000 L. Harvesting of the microalgal biomass was carried by pH-induced flocculation using NaOH at pH 12 for 12 h following Koley, Prasad, Bagchi, & Mallick (2017).…”
Section: Culture Conditions For the Experimental Organismmentioning
confidence: 99%